INTEGRASI ILMU PENGETAHUAN DAN AGAMA DI PONDOK PESANTREN: STUDI KASUS PEMAHAMAN EPISTEMOLOGI GURU MELALUI PENDEKATAN FENOMENOLOGI - Muhammad Iksan Fahmi Nursyeha (Hijri, 2025)
This study examines the integration of general knowledge and religious teachings in Islamic boarding schools (pesantren), focusing on the epistemological perspectives of teachers. The research, conducted at Pondok Pesantren Darul Quran Insan Cendekia in Sukabumi, uses a phenomenological approach to explore the personal experiences of teachers in blending scientific and religious knowledge. The findings emphasize the crucial role of teachers' epistemology in achieving a harmonious balance between intellect and spirituality. Teachers play a vital role in aligning Islamic values with scientific knowledge, facilitating a comprehensive educational experience that prepares students for both academic and spiritual challenges. Despite progress, challenges remain, such as limited expertise in general sciences and teaching skills, which highlight the need for ongoing teacher training and professional development. Integrating religious teachings with modern educational tools, like technology, is also crucial to improve teaching effectiveness. The study highlights how strong epistemological understanding enables the integration of divine revelation (naqli) and human reasoning (aqli), creating a cohesive and holistic learning system. The research contributes to the broader conversation on integrative education, providing insights on how to practically implement such models and overcome obstacles. It advocates for a modern pesantren model that fosters intellectual skills and moral values, preparing students to succeed in a globalized world while maintaining their Islamic identity.